Investigating cylinder deactivation as a low fuel-penalty thermal management strategy for heavy-duty diesel engines - Hushion, Christian; Thiruvengadam, Arvind; Pondicherry, Rasik; Thompson, Gregory; Baltrucki, Justin; Janak, Robb; Lee, Justin; Farrell, Lisa (Frontiers in Mechanical Engineering, 2022)
The upcoming ultra-low-NOx (oxides of nitrogen) emissions standard and in-use NOx emissions requirement requires engine manufacturers to further reduce tailpipe NOx emissions by over 90% from the current United States Environmental Protection Agency (USEPA) 2010 heavy-duty emissions standard. To meet ultra-low NOx standards, significant improvements to the NOx reduction capability of the Selective Catalytic Reduction (SCR) system are required. Low-temperature exhaust conditions and the associated fuel penalty in increasing the exhaust temperatures for improving catalyst activity is an engineering challenge to balance lowering NOx emissions while lowering fuel consumption. Cylinder Deactivation (CDA) in diesel engines has shown the ability to increase exhaust temperatures while maintaining a zero-fuel penalty. This study details the results of the performance of CDA hardware installed in a modern heavy-duty diesel engine. The study was aimed at developing steady-state engine calibrations to maximize exhaust temperatures while realizing a zero-fuel penalty or improved BTE operation during low-load engine operating conditions for an on-road heavy-duty diesel engine. In addition, the study demonstrated the effect of CDA on lowering aftertreatment cooldown during motoring operations. The results of the study showed close to a 100 °C increase in turbine out temperatures (TOT) at idle, 1000 rpm, and 1200 rpm engine speeds with engine load at 10% and 20% of rated torque. The results also showed that deactivating three of the six cylinders during motoring operation of the low-load cycle delayed aftertreatment cooldown and maintained exhaust temperatures above the SCR activity threshold for a longer duration.